Formulation and Evaluation of Cream Turmeric Extract Preparations from Turmeric Rhizomes (Curcuma domestica Val.) - Estefania, Kaban Vera; Silalahi, Jansen; Sumaiyah, Sumaiyah; Satria, Denny (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
The use of plants as a method of herbal treatment is a step that is currently being developed by many researchers to produce effective and minimal side effects. Turmeric is one of the most widely used cooking spices by the people of Indonesia. The main ingredients possessed by turmeric include curcumin (77%), demethoxy (17%) and bisdemethoxy (3%). One of the pharmaceutical preparations with a topical delivery system is a cream preparation which is a semi-solid dosage form, containing one or more drug ingredients dissolved or dispersed in an appropriate base material. Turmeric can be formulated in various preparations, one of which is a cream dosage form. The advantage of using cream preparations is that they are practical, easy to wash and clean. The purpose of this study was to formulate turmeric extract in a cream preparation. The results of the evaluation test showed that the formula produced a cream with a yellow-orange color, a characteristic odor of turmeric, and a preparation with a semisolid cream texture, had good homogeneity, good dispersing ability, the pH of the preparation was 5.84; 6.32; 6.24; 5,94;5,94 and the type of emulsion is O/W (Oil in Water).